Blue light-promoted cross-coupling of aryldiazoacetates and diazocarbonyl compounds. Issue 64 (24th July 2018) - Xiao, Tiebo; Mei, Mingjing; He, Yuwei; Zhou, Lei
Abstract : A blue light-promoted cross-coupling of two distinct diazo compounds was described. The reaction produces E -configured trisubstituted alkenes in good yields in the absence of catalysts and additives. The reactive free carbene intermediates were generated via selective photolysis of one of the two diazo compounds upon blue light irradiation. Abstract : A blue light-promoted cross-coupling of two distinct diazo compounds was described. The reaction produces E -configured trisubstituted alkenes in good yields in the absence of catalysts and additives. The reactive free carbene intermediates were generated via selective photolysis of one of the two diazo compounds upon blue light irradiation.